Comparative transcriptome combined with morphophysiological analyses revealed the molecular mechanism underlying Tetrahymena thermophila predation-induced antiphage defense in Aeromonas hydrophila. Issue 1 (31st December 2022) - Dong, Yuhao; Liu, Jin; Nie, Meng; Zhao, Dan; Huang, Hao; Geng, Jinzhu; Wan, Xihe; Lu, Chengping; Liu, Yongjie
ABSTRACT: Protozoan predation has been demonstrated to be a strong driving force for bacterial defence strategies in the environment. Our previous study demonstrated that Aeromonas hydrophila NJ-35, which evolved small-colony variants (SCVs), displayed various adaptive traits in response to Tetrahymena thermophila predation, such as enhanced phage resistance. However, the evolutionary mechanisms are largely unknown. In this study, we performed a genome- and transcriptome-wide analysis of the SCV1, representing one strain of the SCVs, for identification of the genes of mutation and altered expression underlying this phage resistance phenotype. Our study demonstrated that phage resistance caused by T. thermophila predation was due to the downregulation of a flagellar biosynthesis regulator, flhF, in SCV1. Interestingly, we confirmed that phage resistance in SCV1 was not straightforwardly attributable to the absence of flagella but to FlhF-mediated secretion of extracellular protein that hinders phage adsorption. This finding improves our understanding of the mechanisms by which A. hydrophila lowers the susceptibility to phage infection under predation pressure, and highlights an important contribution of bacterium–protozoan interactions in driving the adaptive evolution of pathogens in complex environments.